Effect of Ride-Hailing Service Factors on Generation Z’s Satisfaction in Kathmandu Valley - Sikhrakar, Lijah; Manandhar, Bijaya; Bhusal, Navraj (Chaturbhujeshwar Academic Journal, 2024)
This study analyzed the factors that affect Gen Z’s satisfaction level with ride-hailing services in Kathmandu Valley. It used a cross-sectional research design, where data was collected using a structured questionnaire from 188 respondents residing in Kathmandu Valley during the study period. The samples were selected using the convenience sampling technique. The descriptive statistics Pearson’s correlation and hierarchical regression were adopted for data analysis. The results show that all the variables, driver’s attitude, service reliability, and price, were positively correlated with Gen Z’s satisfaction. Among these variables, the driver’s attitude stood out as the most influencing factor, followed by price and service reliability for inducing satisfaction among Gen Z. The study can be useful in comprehending the major factors for Gen Z’s satisfaction in terms of ride-hailing services, which can be used in their strategic decision-making. Future researchers can utilize the findings and broaden the scope in terms of variables, methods, and population for further knowledge elaboration.